2010
DOI: 10.1111/j.1467-8624.2010.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Physiological and Cognitive Regulatory Systems: Infant Sleep Regulation and Subsequent Executive Functioning

Abstract: The aim of this report was to investigate the prospective links between infant sleep regulation and subsequent executive functioning (EF). The authors assessed sleep regulation through a parent sleep diary when children were 12 and 18 months old (N = 60). Child EF was assessed at 18 and 26 months of age. Higher proportions of total sleep occurring at night time, at both 12 and 18 months, were related to better performance on executive tasks, especially those involving a strong impulse control component. Most r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
153
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(171 citation statements)
references
References 87 publications
16
153
1
1
Order By: Relevance
“…There is a well-documented association between short sleep duration and obesity in young children (Chen et al, 2008), and one study found that the 30-min difference in sleep duration at ages 3–5 years, associated with obesity at age 9.5 years, was almost entirely due to napping (Agras, Hammer, McNicholas, & Kraemer, 2004). However, higher proportion of total sleep occurring at night has been positively associated with executive functioning in infants (Bernier, Carlson, Bordeleau, & Carrier, 2010), and daytime napping was negatively correlated with neurocognitive function in pre-schoolers (Lam, Mahone, Mason, & Scharf, 2011). Although these findings indicate that cessation of napping is a marker for brain development, we have previously reported that in our sample of children, positive parental attitude towards napping was associated with longer child nap duration, suggesting that napping may be influenced by parental attitudes as well as being biologically determined (Jones & Ball, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There is a well-documented association between short sleep duration and obesity in young children (Chen et al, 2008), and one study found that the 30-min difference in sleep duration at ages 3–5 years, associated with obesity at age 9.5 years, was almost entirely due to napping (Agras, Hammer, McNicholas, & Kraemer, 2004). However, higher proportion of total sleep occurring at night has been positively associated with executive functioning in infants (Bernier, Carlson, Bordeleau, & Carrier, 2010), and daytime napping was negatively correlated with neurocognitive function in pre-schoolers (Lam, Mahone, Mason, & Scharf, 2011). Although these findings indicate that cessation of napping is a marker for brain development, we have previously reported that in our sample of children, positive parental attitude towards napping was associated with longer child nap duration, suggesting that napping may be influenced by parental attitudes as well as being biologically determined (Jones & Ball, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies with both infants and school-age children support the role of sleep for normal adaptive functioning across cognitive (e.g., Bernier, Carlson, Bordeleau, & Carrier, 2010;Buckhalt, El-Sheikh, Keller, & Kelly, 2009; see Dewald, Meijer, Oort, Kerkhof, & Bögels, 2010 for a recent review and meta-analyses) and socioemotional functioning domains (e.g., Chorney, Detweiler, Morris, & Kuhn, 2008;El-Sheikh, Kelly, Buckhalt, & Hinnant, 2010; and see Astill, Van der Heijden, Van IJzendoorn, & Van Someren, 2012, for a meta-analysis). These studies suggest that normative differences in sleep duration and quality are associated with a range of differences in adaptive functioning for school-age children.…”
Section: Sleep As a Support For Social Competence Peer Relations Anmentioning
confidence: 95%
“…Research with infants and very young children has supported this idea, finding that early sleep predicts later EC. Bernier and colleagues found that sleep at age 1 was associated with EC performance at ages 18 months, 2 years, and 4 years (Bernier et al, 2010(Bernier et al, , 2013. Sadeh and colleagues (2015) report that sleep quality at 1 year significantly predicts attention and behavioral regulation at 3-4 years of age.…”
mentioning
confidence: 94%